Identifying challenges and co-imagining futures for a design for health network. Issue 2 (4th May 2021) - Nakarada-Kordic, Ivana; Reay, Stephen; Craig, Claire; Collier, Guy; Khoo, Cassandra; Fisher, Helen; Kayes, Nicola
Abstract: For the emerging field of Design for Health (D4H) to realize its potential, it is necessary to identify and address existing challenges faced by its community. The few papers that have identified challenges and opportunities in Design for Health confirm that healthcare is a challenging environment for designers to work in. In part this is because design is often misunderstood by health professionals. This paper describes a study that sought to understand the challenges and opportunities for a future D4H Global Network as identified by workshop participants spanning different backgrounds, contexts, and countries. Qualitative data from 59 participants were collected during the D4H Symposium 2019 workshop and analysed using a thematic method. Practical constraints identified by participants included lack of resources and differing regulatory and governance frameworks which acted as barriers to building and participating in transdisciplinary projects in this space. However, participants also acknowledged that broader philosophical barriers arising as a consequence of siloed perspectives and different research paradigms between design and health were equally problematic. Despite these challenges, the overall findings were inherently optimistic as participants co-imagined broad opportunities for a future global network and collectively identified targeted solutions for 'breaking the "normal" and "doing things differently"'.